Ultra-high molecular weight polyethylene / MXene porous material and preparation method thereof

By dispersing MXene, di-tert-amylphenylphenol and ultra-high molecular weight polyethylene powder in an organic solvent, and subjecting to low-temperature freezing and vacuum freeze-drying treatment, ultra-high molecular weight polyethylene/MXene porous materials with good hydrophobicity and porous structure were prepared, which solved the problem of difficulty in adsorbing high viscosity crude oil, and achieved rapid adsorption and viscosity reduction of high viscosity crude oil.

CN115028884BActive Publication Date: 2025-04-29ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210811091.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-04-29
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively adsorb high viscosity crude oil pollutants, and the preparation method of ultra-high molecular weight polyethylene porous materials is single and has low porosity.

Method used

Ultra-high molecular weight polyethylene/MXene porous material was prepared by dispersing MXene, di-tert-amylphenol and ultra-high molecular weight polyethylene powder in an organic solvent, and freeze-drying after low temperature freeze and vacuum freeze drying.

Benefits of technology

The prepared porous materials have good hydrophobicity and three-dimensional porous structure, which can quickly adsorb high-viscosity crude oil pollutants and reduce crude oil viscosity through photothermal conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115028884B_ABST
    Figure CN115028884B_ABST
Patent Text Reader

Abstract

A method for preparing an ultra-high molecular weight polyethylene / MXene porous material comprises the following steps: 1) dispersing MXene, di-tert-amylphenol and ultra-high molecular weight polyethylene powder in an organic solvent to obtain a dispersion; 2) freezing the dispersion at low temperature and then performing vacuum freeze drying to obtain an ultra-high molecular weight polyethylene / MXene porous material. The ultra-high molecular weight polyethylene / MXene porous material obtained by the present invention has good hydrophobicity, a three-dimensional porous structure and good photothermal conversion performance, can quickly heat up, reduce crude oil viscosity, and can quickly adsorb both low-viscosity and high-viscosity crude oil pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a method for preparing an ultra-high molecular weight polyethylene / MXene porous material. Background Art

[0002] With the development of contemporary production technology, environmental issues have always been the focus of people's attention. Due to the acceleration of urbanization and offshore oil exploration, the discharge of oily pollutants and offshore oil spills have become more and more serious, leading to large-scale water pollution. While destroying the marine ecological environment, oil pollutants also interfere with the feeding and reproduction of organisms. At present, the main methods for treating oily pollutants are gravity separation, dispersants, biodegradation and adsorption. Among them, the adsorption method has attracted much attention due to its simple operation and high separation efficiency. Polymer porous materials with three-dimensional porous structures and high porosity are one of the current research hotspots of adsorption-type oil-water separation materials. However, at present, due to the high viscosity of crude oil at room temperature, it is difficult for ordinary oil-water separation materials to directly achieve the adsorption of high-viscosity crude oil.

[0003] Ultra-high molecular weight polyethylene has broad application prospects in the field of oil-water separation due to its special wettability. However, the high melt viscosity of ultra-high molecular weight polyethylene makes it difficult to form by conventional mechanical processing. At present, ultra-high molecular weight polyethylene is mainly prepared by gel spinning to produce high-performance fibers, and its porous materials still face problems such as a single preparation method and low product porosity. Summary of the invention

[0004] The embodiment of the present invention provides a method for preparing an ultra-high molecular weight polyethylene / MXene porous material, which is used to alleviate the current technical problem that high-viscosity crude oil is difficult to adsorb.

[0005] In order to solve the above technical problems, this application provides the following technical solutions:

[0006] The present application provides a method for preparing ultra-high molecular weight polyethylene / MXene porous material.

[0007] 1) dispersing MXene, di-tert-amylphenol and ultra-high molecular weight polyethylene powder in an organic solvent to obtain a dispersion;

[0008] 2) The dispersion is cryogenically frozen and then subjected to vacuum freeze-drying treatment to obtain an ultra-high molecular weight polyethylene / MXene porous material.

[0009] In some embodiments, the steps of preparing the dispersion include:

[0010] The MXene and the di-tert-amylphenol are dispersed in an organic solvent, and ultrasonicated for 1 to 2 hours using an ultrasonic cell crusher; then the ultra-high molecular weight polyethylene powder is added, and ultrasonication is continued for 1 to 2 hours; then the dispersion is placed in an oil bath at 130 to 135° C. and heated for 2 to 3 hours.

[0011] In some specific embodiments of the present invention, the concentration of the ultra-high molecular weight polyethylene in the dispersion is 3-4 mg / mL, the amount of the MXene is 3-6 wt% of the mass of the ultra-high molecular weight polyethylene, and the amount of the di-tert-amylphenol is 10-30 wt% of the mass of the ultra-high molecular weight polyethylene.

[0012] More preferably, the amount of MXene used is 5 wt% of the mass of the ultra-high molecular weight polyethylene, and the amount of di-tert-amylphenol used is 25 wt% of the mass of the ultra-high molecular weight polyethylene.

[0013] In some specific embodiments of the present invention, the organic solvent is any one of xylene, p-xylene or decalin.

[0014] In some specific embodiments of the present invention, the low-temperature freezing temperature in step 2) is -20 to -4°C, the freezing time is 12 to 24 hours, the vacuum degree of vacuum freeze-drying is maintained below 20 Pa, the freeze-drying temperature is maintained below -70°C, and the drying time is not less than 72 hours.

[0015] The present application provides a method for preparing an ultra-high molecular weight polyethylene / MXene porous material, wherein the ultra-high molecular weight polyethylene / MXene porous material is prepared by any of the above-mentioned preparation methods.

[0016] The present application provides a method for preparing an ultra-high molecular weight polyethylene / MXene porous material, wherein MXene, di-tert-amylphenol and ultra-high molecular weight polyethylene powder are dispersed in an organic solvent to obtain a dispersion; the dispersion is cryogenically frozen and then subjected to vacuum freeze drying to obtain an ultra-high molecular weight polyethylene / MXene porous material. The ultra-high molecular weight polyethylene / MXene porous material has good hydrophobicity and a three-dimensional porous structure, and can not only be applied to low-viscosity oil-water separation, but also can quickly heat up and reduce crude oil viscosity due to its good photothermal conversion performance, and can quickly adsorb high-viscosity crude oil pollutants.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The problem of poor dispersibility of the ultra-high molecular weight polyethylene / MXene porous material filler in ultra-high molecular weight polyethylene is solved by introducing di-tert-amylphenol as a dispersant to promote the dispersion of MXene, so that a uniformly dispersed ultra-high molecular weight polyethylene / MXene dispersion can be obtained by traditional solution blending;

[0019] 2. The ultra-high molecular weight polyethylene / MXene porous material prepared by the present invention has an absorptivity of 99.97% and a reflectivity of 0.02%, which is mainly due to the interaction between di-tert-amylphenol and MXene, which avoids the agglomeration of MXene in the ultra-high molecular weight polyethylene matrix during solution blending;

[0020] 3. The ultra-high molecular weight polyethylene / MXene porous material prepared by the present invention has the ability of photothermal conversion, and can effectively utilize the light in the ultraviolet band to convert it into thermal energy. This function is derived from the photothermal conversion effect of MXene and di-tert-amylphenol and the synergistic effect between them.

[0021] 4. The ultra-high molecular weight polyethylene / MXene porous material prepared by the present invention has excellent photothermal conversion function, and can reduce its viscosity by increasing the temperature of crude oil, thereby realizing the adsorption treatment of high-viscosity crude oil; 5. The method of the present invention is easy to operate, low in cost, short in cycle, and suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 is a microscopic morphology of the porous material provided in Example 1 of the present invention;

[0024] Figure 2 is the absorptivity and reflectivity of the porous material provided in Example 1 of the present invention and Comparative Example 1;

[0025] Figure 3 It is the low adhesion behavior of water droplets on the surface of porous materials provided by Example 1 of the present invention;

[0026] Figure 4 is the change of water contact angle under different pH conditions provided in Example 1 of the present invention;

[0027] Figure 5 is the adsorption multiple of different types of oils by the porous material provided in Example 1 of the present invention;

[0028] Figure 6a The temperature change (100 mW cm) of the porous materials provided in Example 1, Example 3 and Comparative Example 1 of the present invention under a simulated sunlight environment -2 );

[0029] Figure 6b This is an infrared thermal imaging picture of the porous material at 60 seconds provided in Example 1, Example 3 and Comparative Example 1 of the present invention;

[0030] Figure 7a The temperature change (100 mW cm) of the porous materials provided in Comparative Examples 2 to 4 of the present invention under simulated sunlight environment -2 );

[0031] Figure 7b This is the infrared thermal imaging picture of the porous material at 60s provided in Comparative Examples 2 to 4 of the present invention;

[0032] Figure 8a 1 is a diagram of a crude oil adsorption mass change test device provided in Example 1 of the present invention and Comparative Example 5;

[0033] Figure 8b is the mass change of the porous materials provided by Example 1 of the present invention and Comparative Example 5. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0035] The present application provides a method for preparing an ultra-high molecular weight polyethylene / MXene porous material, wherein MXene, di-tert-amylphenol and ultra-high molecular weight polyethylene powder are dispersed in an organic solvent to obtain a dispersion, wherein the weight fraction of MXene in the dispersion is 3 to 6 wt%, and the weight fraction of di-tert-amylphenol is 10 to 30 wt%; the dispersion is cryogenically frozen and then subjected to vacuum freeze-drying treatment to obtain an ultra-high molecular weight polyethylene / MXene porous material.

[0036] Example 1

[0037] The preparation method of the ultra-high molecular weight polyethylene / MXene porous material in this embodiment has the following specific steps:

[0038] 1) Dispersing MXene, di-tert-amylphenol and ultra-high molecular weight polyethylene powder in an organic solvent to obtain a dispersion:

[0039] First, add 15 mg of MXene (5 wt% of the mass of ultra-high molecular weight polyethylene) and 75 mg of di-tert-amylphenol (25 wt% of the mass of ultra-high molecular weight polyethylene) to p-xylene (80 mL), use an ultrasonic cell crusher to sonicate for 1 hour to completely mix MXene and di-tert-amylphenol, then add 300 mg of ultra-high molecular weight polyethylene powder, and continue to sonicate for 1 hour to fully mix the ultra-high molecular weight polyethylene powder and MXene. Put the mixed solution into a 130°C oil bath and heat for 2 hours until it is completely dissolved;

[0040] 2) The dispersion is frozen at low temperature and then subjected to vacuum freeze drying to obtain an ultra-high molecular weight polyethylene / MXene porous material:

[0041] The dispersion was first placed in a -4°C refrigerator for 12 h and then freeze-dried in a freeze dryer at 8 Pa and -80°C for 72 h.

[0042] Performance test of the composite film prepared in this example:

[0043] 1. The structure of the ultra-high molecular weight polyethylene / MXene porous material prepared in this example was observed using a scanning electron microscope: Figure 1 As shown, the ultra-high molecular weight polyethylene / MXene porous material forms a three-dimensional porous structure with micron pores of 10 to 50 μm in diameter. The pore walls are relatively smooth, without agglomeration or irregular protrusions formed by fillers on the pore walls, indicating that MXene nanosheets and di-tert-amylphenol are evenly dispersed in the porous material.

[0044] 2. The absorbance and reflectance of the ultra-high molecular weight polyethylene / MXene porous material prepared in this embodiment at 300-800 nm were measured using an ultraviolet-near infrared absorption spectrometer: Figure 2 As shown, the absorption rate of the porous material reaches 99.97%, indicating that the porous material can basically completely absorb visible light, and the reflectivity of the porous material is as low as 0.02%;

[0045] 4. The wettability of the ultra-high molecular weight polyethylene / MXene porous material prepared in this example was tested using a contact angle meter: a water drop was dropped onto the sample surface through a contact angle meter. After contact, the water drop rose with the needle tube due to its low adhesion and did not stay on the sample surface (e.g. Figure 3 As shown in Figure 2, under different pH environments, including strong acid and strong alkali environments, the porous material still maintains stable hydrophobicity, is resistant to strong acids and alkalis, and exhibits good environmental adaptability (as shown in Figure 2). Figure 4 shown);

[0046] 5. The adsorption performance of the ultra-high molecular weight polyethylene / MXene porous material prepared in this example was tested: Figure 5As shown in Figure 2, due to different densities and viscosities, the adsorption multiples of porous materials for organic solvents and oils vary greatly, and the adsorption multiple for cyclohexane is the lowest, which is 33.99 g / cm2. -1 The maximum adsorption multiple of carbon tetrachloride is 80.49gg -1 At the same time, in addition to organic solvents, the engine oil can also reach 64.09gg -1 The adsorption multiple is 1.1, so it can be used for oil-water separation of different types of oil-water mixtures;

[0047] 6. The photothermal performance of the ultra-high molecular weight polyethylene / MXene porous material prepared in this example was tested: the temperature of the porous material could be raised to 65.0°C ( Figure 6a ), corresponding to the infrared thermal imaging image, can more clearly show the change of surface temperature of porous materials ( Figure 6b );

[0048] 7. The crude oil adsorption performance of the ultra-high molecular weight polyethylene / MXene porous material prepared in this example was tested: as shown in FIG8 , at 100 mW cm -2 Under light conditions, the mass of the porous material rapidly increases to a saturated state within 360 seconds. Subsequently, due to partial evaporation of crude oil under light conditions, the mass slowly decreases. Under the saturated adsorption state (360 seconds), the adsorption multiple of crude oil can reach 22.51 gG. -1 .

[0049] Example 2

[0050] The preparation method of the ultra-high molecular weight polyethylene / MXene porous material in this embodiment has the following specific steps:

[0051] 1) Dispersing MXene, di-tert-amylphenol and ultra-high molecular weight polyethylene powder in an organic solvent to obtain a dispersion:

[0052] First, add 15 mg of MXene (5 wt% of the mass of ultra-high molecular weight polyethylene) and 75 mg of di-tert-amylphenol (25 wt% of the mass of ultra-high molecular weight polyethylene) into p-xylene (80 mL), use an ultrasonic cell crusher to ultrasonicate for 1 hour to completely mix the MXene and di-tert-amylphenol, then add 300 mg of ultra-high molecular weight polyethylene powder, and continue to ultrasonicate for 1 hour to fully mix the ultra-high molecular weight polyethylene powder and MXene, put the mixed solution into a 130°C oil bath and heat for 2 hours until it is completely dissolved.

[0053] 2) The dispersion is freeze-dried to obtain an ultra-high molecular weight polyethylene porous material:

[0054] The dispersion was first frozen in a -10°C refrigerator and then freeze-dried in a freeze dryer at 8Pa and -80°C for 72 h.

[0055] The properties of the ultra-high molecular weight polyethylene / MXene porous material prepared in this example are basically equivalent to those in Example 1.

[0056] In other embodiments, in step 1), the temperature of the oil bath may also be 130-135°C.

[0057] In step 2), the freezing temperature of the refrigerator can also be other temperatures between -20 and -4°C.

[0058] In step 2), the freeze-drying temperature can also be other temperatures between -75 and -80°C, the vacuum degree is maintained below 20 Pa, and the drying time is not less than 72 hours.

[0059] Example 3

[0060] Example 3 is substantially the same as Example 1, except that 9 mg of MXene (3 wt% of the mass of the ultra-high molecular weight polyethylene) and 45 mg of di-tert-amylphenol (15 wt% of the mass of the ultra-high molecular weight polyethylene) were added when preparing the dispersion.

[0061] The photothermal performance of the ultra-high molecular weight polyethylene / MXene porous material prepared in this example was tested: the temperature of the porous material could be raised to 63.8°C ( Figure 6a ), the photothermal conversion performance of the ultra-high molecular weight polyethylene / MXene porous material prepared in Example 3 is slightly lower than that in Example 1, but still has good photothermal conversion performance (Figure 6).

[0062] Comparative Examples 1 to 4

[0063] The ultra-high molecular weight polyethylene / MXene porous material of this comparative example is different from that of Example 1 in that different mass fractions of MXene and di-tert-amylphenol (Table 1) are added to p-xylene (80 mL), and the rest is the same as that of Example 1.

[0064] Table 1 Contents of MXene and di-tert-amylphenol in Comparative Examples 1 to 4

[0065] Samples MXene (wt%) Di-tert-amylphenol (wt%) Comparative Example 1 1 5 Comparative Example 2 3 0 Comparative Example 3 3 3 Comparative Example 4 3 9

[0066] The absorbance and reflectance of the ultra-high molecular weight polyethylene / MXene porous material prepared in Comparative Example 1 at 300-800 nm were measured using an ultraviolet-near infrared absorption spectrometer: Figure 2As shown, the absorption rate of the porous material reaches 81.25%, which is lower than the absorption rate of the porous material in Example 1 (99.97%), and the reflectivity of the porous material is as low as 6.85%, which is higher than the reflectivity of the porous material prepared in Example 1 (0.02%).

[0067] The photothermal properties of the ultra-high molecular weight polyethylene / MXene porous materials prepared in Comparative Examples 1 to 4 were tested: the temperature of the porous materials could be raised to 50.1°C, 52.7°C, 52.6°C, 55.2°C ( Figure 6a , 7a), corresponding to the infrared thermal imaging picture as Figure 6b , as shown in 7b, its photothermal conversion performance is worse than that of Example 1.

[0068] Comparative Example 5

[0069] The ultra-high molecular weight polyethylene / MXene porous material of this comparative example is different from that of Example 1 in that no light irradiation is performed during the crude oil adsorption performance test, and the rest is the same as that of Example 1.

[0070] like Figure 8b As shown in Figure 2, the crude oil adsorption capacity tested by this method increased slowly, and the crude oil adsorption multiple reached 13 g g after 1200 s. -1 .

[0071] Comparative Example 6

[0072] The ultra-high molecular weight polyethylene / MXene porous material in this comparative example is different from that in Example 1 in that 300 mg of ultra-high molecular weight polyethylene powder is first added to p-xylene (80 mL), and ultrasonic cell crusher is used for 1 hour, and then 5 wt% of MXene and 25 wt% of di-tert-amylphenol are added, and ultrasonication is continued for 1 hour.

[0073] The MXene in the ultra-high molecular weight polyethylene / MXene porous material prepared by this method is unevenly dispersed and cannot meet the effect of uniform distribution of MXene.

[0074] The above is a detailed introduction to the preparation method of an ultra-high molecular weight polyethylene / MXene porous material provided in an embodiment of the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A method for preparing ultra-high molecular weight polyethylene / MXene porous material, characterized in that: The following steps are involved: 1) Dispersing MXene and di-tert-amylphenol in an organic solvent and ultrasonicating them for 1 to 2 hours using an ultrasonic cell crusher; 2) adding ultra-high molecular weight polyethylene powder, continuing ultrasonication for 1 to 2 hours, and then heating for 2 to 3 hours until completely dissolved; the concentration of the ultra-high molecular weight polyethylene is 3 to 4 mg / mL, the amount of the MXene is 3 to 6 wt% of the mass of the ultra-high molecular weight polyethylene, and the amount of the di-tert-amylphenol is 10 to 30 wt% of the mass of the ultra-high molecular weight polyethylene; 3) The dispersion is cryogenically frozen and then subjected to vacuum freeze-drying to obtain an ultra-high molecular weight polyethylene / MXene three-dimensional porous material.

2. The method for preparing ultra-high molecular weight polyethylene / MXene porous material according to claim 1, characterized in that: The organic solvent is any one of xylene, p-xylene or decalin.

3. The method for preparing ultra-high molecular weight polyethylene / MXene porous material according to claim 1, characterized in that: In step 3), the temperature of low-temperature freezing is -20 to -4°C, and the freezing time is 12 to 24 hours.

4. The method for preparing ultra-high molecular weight polyethylene / MXene porous material according to claim 1, characterized in that: In step 3), the vacuum degree of vacuum freeze drying is maintained below 20 Pa, the freeze drying temperature is maintained below -70°C, and the drying time is not less than 72 hours.

5. An ultra-high molecular weight polyethylene / MXene porous material, characterized in that: The ultra-high molecular weight polyethylene / MXene porous material is prepared by any preparation method according to claims 1-4.

6. Application of the ultra-high molecular weight polyethylene / MXene porous material according to claim 5 in the field of oil-water separation.

Citation Information

Patent Citations

  • Ultra-high molecular weight polyethylene / MXene composite film and preparation method thereof

    CN112679767A

  • Light-driven oil absorption MXene modified melamine sponge and preparation method thereof

    CN114452960A